Distortion of homeostatic signaling proteins by simulated microgravity in rat hypothalamus: A16O/18O‐labeled comparative integrated proteomic approach. Issue 2 (15th January 2014) - Iqbal, Javed; Li, Wang; Hasan, Murtaza; Juan Li, Yu; Ullah, Kaleem; Yun, Wang; Awan, Umer; Qing, Hong; Deng, Yulin
<x xml:space="preserve">Abstract</x> Microgravity generates oxidative stress in central nervous system, causing distortion of various vital signaling cascades involved in many homeostatic functions. Here, we performed comparative 16O/18O labeled integrated proteomic strategy to observe the differential expression of signaling proteins involved in homeostasis. In this study, rat‐tail suspension model is employed to induce simulated microgravity in CNS. By wide proteomic analysis, total of 35 and 97 significantly differentially expressed proteins were found by HPLC/ESI‐TOF and HPLC‐Q‐TOF analysis, respectively. Among the total of 132 proteins quantified, 25 proteins were found related to various signaling cascades. Protein Thy‐1, 14‐3‐3 gamma, 14‐3‐3 epsilon, 14‐3‐3 theta, 14‐3‐3 eta, and 14‐3‐3 beta/alpha proteins, calmodulin and calcium/calmodulin‐dependent protein kinase type‐II subunit beta were found upregulated under the influence of simulated microgravity. These proteins are found involved in disrupting homeostatic pathways like sleep/wake cycle, drinking behavior, hypothalamic‐pituitary‐adrenocortical regulation and fight and/or flee actions under stress. Furthermore, MS results for protein Thy‐1 were verified by Western blot analysis showing the quantification accuracy of MS instruments. Results presented here will serve as means to understand the mechanism of action of microgravity and further reference for future detailed study of consequences of microgravity on astronauts and their possible countermeasures.